Respuesta :

Answer:

a) [tex]a_n=3n-1[/tex]

b) [tex]a_n=2n+7[/tex]

Step-by-step explanation:

This is just an arithmetic sequence. The generic form of an arithmetic sequence is: [tex]a_n=a_1+d(n-1)[/tex] , where [tex]a_1[/tex] is the first term of the sequence and d is the common difference.

a) Here, we can see that the common difference is 3 (because 5 - 2 = 3, 8 - 5 = 3, etc). So, d = 3. Also, the first term is 2, so a_1 = 2. Now, we can just write our expression:

[tex]a_n=2+3(n-1)[/tex]

[tex]a_n=3n-1[/tex]

b) Here, the common difference is 2 (since 11 - 9 = 2, 13 - 11 = 2, etc). So, d = 2. Also, the first term is 9, so a_1 = 9. Now our expression is:

[tex]a_n=9+2(n-1)[/tex]

[tex]a_n=2n+7[/tex]

Hope this helps!

Answer:

a) 3n - 1

b) 2n + 7

Step-by-step explanation:

a) a = 2

d = 5 - 2 = 3

An = 2 + 3(n - 1)

= 2 + 3n - 3

= 3n - 1

b) a = 9

d = 11 - 9 = 2

An = 9 + 2(n - 1)

9 + 2n - 2

2n + 7

ACCESS MORE